Помогите решить 2 ПРИМЕРА!!!!))

1)100^x=0,1*(10^x-1)^5
2)3^(2x) -2 * 3^(2x-2) -2 * 3^(2x-1) = 1

1

Ответы и объяснения

Лучший Ответ!
  • Yena
  • главный мозг
2013-02-15T20:11:23+04:00

100^x=0,1*(10^x-1)^5

10^{2x}=10^{-1}*10^{5x-5}

10^{2x}=10^{-1+5x-5}

10^{2x}=10^{5x-6}

2x=5x-6

3x=6

x=2


3^(2x) -2 * 3^(2x-2) -2 * 3^(2x-1) = 1

3^{2x}-2*3^{2x}*3^{-2}-2*3^{2x}*3^{-1}=1

3^{2x}*(1-2*\frac{1}{9}-2*\frac{1}{3})=1

3^{2x}*(1-\frac{2}{9}-\frac{2}{3})=1

3^{2x}*\frac{1}{3}=1

3^{2x}=3^{1}

2x=1

x=\frac{1}{2}